Police’s Public Relations to Enhance Mutual Understanding in Indonesia - Frizki Yulianti Nurnisya; Suriati Binti Saad; Mahyuddin Ahmad Rahman (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
The study of police public relations is a new phenomenon that has been rising lately. Indeed, along with the growth of modernity, increasing disputes, the need for convergence, and the community environment, there have been increasing demands from the public for the police to make changes in their actions and attitude when dealing with the community. This research uses qualitative methodology as it explores activities carried out by police institutions. Hence, the a case study is a right research method because this research explores the government’s agency, especially within public policy. The research result shows that to complete this job correctly, the police need public support, and to maximize this support, the police need the functions of police’s public relations at all levels, from the National Police Headquarters to the District Police.